A new hybrid BIPV array for enhancing maximum power with reduced mismatch losses under extreme partial shading scenarios. Issue 2 (15th June 2022) - Sarkar, Debayan; Sadhu, Pradip Kumar
ABSTRACT: Building integrated photovoltaic (BIPV) systems are gaining major attention in modern cities due to the absence of free space to install ground-mounted photovoltaic (PV) plants. A large interconnected BIPV array (liBA) is essential for standalone and grid-connected BIPV systems. The major problem with liBA is the partial shading (PS) phenomenon that increases the mismatch losses (MmLs) and reduces the maximum power (MP) output. Modelling, simulation, and performance analysis of a novel 7 × 5 and 7 × 8 hybrid triple-tied total-cross-tied (TrTd-TtCrTd) fixed BIPV array for increasing MP with reduced MmLs under extreme PS conditions are the main goals of this research paper. In addition, existing hybrid arrays such as series-parallel total-cross-tied (SePl-TtCrTd), bridge-linked total-cross-tied (BdLk-TtCrTd), and honey-combed total-cross-tied (HnCb-TtCrTd), as well as conventional triple-tied (TrTd) and total-cross-tied (TtCrTd), are compared. The simulation results are also validated experimentally using two PS situations. Finally, the global maximum power point (GlMxPoPt), MmLs, fill factor ( FiFa ), and efficiency ( Effy ) are used to evaluate the performance. Under six different extreme PS scenarios, the simulation results show that the proposed 7 × 5 hybrid TrTd-TtCrTd array increases GlMxPoPt by 4.84 %, decreases MmLs by 3.46 %, and increases FiFa and Effy by 2.20 % and 0.34 %, respectively. Under two severe PS scenarios, simulation results show that the proposed 7 × 8 large size hybrid TrTd-TtCrTd array increases GlMxPoPt by 3.43 %, decreases MmLs by 2.29 %, and increases FiFa and Effy by 1.26 % and 0.23 %, respectively. Under two extreme PS scenarios, experimental results indicate that the proposed 7 × 8 hybrid TrTd-TtCrTd solar array increases GlMxPoPt by 2.84 %, decreases MmLs by 2.12 %, and increases FiFa and Effy by 1.82 % and 0.22 %, respectively. The proposed hybrid TrTd-TtCrTd array improves GlMxPoPt, reduces MmLs and improves FiFa and Effy with low wiring requirements under different PS cases.